Direct UV written optical waveguides in flexible glass flat fiber chips - Adikan, Faisal Rafiq Mahamd; Sandoghchi, S.R.; Yi, C.W.; Simpson, R.E.; Mahdi, M.A.; Webb, A.S.; Gates, J.C.; Holmes, C. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
A glass-based substrate technology that fills the gap between a truly flexible extended length distributed sensor medium and the multifunctionality of optical chips is demonstrated. Flat fiber chips will open further degrees of freedom to control the behavior of light via mechanical manipulation. A flexible flat format will also allow straightforward incorporation into smart structures. Coupled with low manufacturing costs, these flexichips can also be a key enabler to disposable high-end sensing devices or fully distributed point sensors. In this study, Bragg gratings were used to demonstrate the optical flatness of the flat fiber core layer. Furthermore, the effective index values obtained from the grating experiment were input into a dynamic model, subsequently proving the influence of the dumbbell-shaped flat fiber cross section on the resultant UV written waveguides. Evanescent field sensing was also demonstrated by adopting a stepped Bragg approach.